Influence of integrity and moral intelligence on authentic leadership and organisational citizenship behaviour - Matsimbe, Cleopatra Meisie Refeloe (Stellenbosch : Stellenbosch University, 2017)
Thesis (MCom)-- Stellenbosch University, 2017.